ESTABLISHING GOOD GOVERNANCE THROUGH VALUE IMPLEMENTATION OF MONEY PRINCIPLES IN PUBLIC PROCUREMENT POLICY CONTEXT - Vincensya Pingkan Meylinda Palar; Kadek Cahya Susila Wibawa; Solechan Solechan (UNISSULA, 2021)
This study aimed to review the application of Value for Money principles in public procurement policy to establish good governance in Indonesia. This research used a normative legal method using library research with legal and historical approaches. The results of this study showed that the implementation of Value for Money in public procurement policy is urgent to be applied, which is to encourage the good public procurement practice and produce the right goods/services based on quality, quantity, time, cost, location, and provider aspects; increase the efficiency of the use of public money, which can suppress budget leaks; improve the effectiveness of state financial management; improve the effectiveness and quality of public services; realize a clean government. Arrangements regarding Value for Money in public procurement policy are very clear by the application of e-procurement and utilization of e-marketplace; sustainable procurement; and the use of domestic products. This research also indicated the real relevance of the implementation of Value for Money principles in public procurement policy to establish good governance in Indonesia.